2017
DOI: 10.1002/ijop.12447
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between collectivism and corruption in American and Chinese books: A historical perspective

Abstract: Previous research on the relationship between collectivism and corruption has not investigated their co-variation over time. In this study, we use Google Ngram Viewer to track the frequency of words related to collectivism and corruption in American books (1800-2000) and in Chinese Books (1970-2008). The results demonstrate that a positive association between the usage of these terms during the periods in both Chinese and American books, with changes in words related to collectivism preceding changes in words … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…One is a dictionary of collectivism used in a prior study (Y. Li et al, 2019). Li and colleagues identified these words in their survey of 38 scales of individualism-collectivism in the literature.…”
Section: Dictionary Validationmentioning
confidence: 99%
“…One is a dictionary of collectivism used in a prior study (Y. Li et al, 2019). Li and colleagues identified these words in their survey of 38 scales of individualism-collectivism in the literature.…”
Section: Dictionary Validationmentioning
confidence: 99%
“…Overall, Google Ngram has allowed scholars to shed further light on various topics such as gender differences [ 17 , 18 , 19 ], emotions [ 20 , 21 , 22 , 45 ], personality [ 23 , 24 ], cognition [ 25 , 26 , 27 ], hypnosis and psychotherapy [ 46 ], moral values [ 47 ], education [ 48 ], nature [ 49 ], astrology and phrenology [ 50 ], and the development of individualism and collectivism (e.g., [ 6 , 7 , 10 , 51 , 52 ]). In this respect, despite limitations, we believe that Google Ngram is a beneficial tool for research purposes and that the procedures presented in this guideline can reinforce the reliability of derived results.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have contended that collectivism is related to phenomena like morality, modernism, religiosity, economic development, social systems, social pathology, and psychological well-being (Hofstede, 2001;Oyserman & Lee, 2008;Triandis, 1995). Scholars have also noted that most advanced and wealthy industrial societies are more individualistic and moral than collectivist societies because collectivism facilitates unethical behavior; in most of the collectivist societies, people with similar (unethical) motives will join hands to pursue immoral practices without fear of being evaluated morally, legally, and socially by their groups (Huang et al, 2015;Li et al, 2019). Past studies revealed the positive association between collectivism and unethical behavior with some exceptions of the countries where political and legal institutions are comparatively stronger (Huang et al, 2015;Zheng et al, 2012).…”
Section: The Moderating Role Of Collectivismmentioning
confidence: 99%
“…This value motivates them to ignore their supervisors' deviant actions, as they want to support their supervisors in all their actions (Fang & Lim, 2002). Li et al (2019) averred that the process of increasing collectivism plays a moderating role in the relationship between modernity and collectivism and suggest exploring the role of collectivism in the mechanisms that lead to unethical behavior in other highly collectivist countries that also have high levels of corruption-like Pakistan. Taking that lead, the present study proposes that, because of their greater acceptance of the unethical behavior of in-group members and their exchange of loyalties, in highly collectivist countries having weak legal institutional structures, leaders with a tendency toward malpractice (Machiavellians) are likely to indulge in unethical behavior.…”
Section: The Moderating Role Of Collectivismmentioning
confidence: 99%